Changing the Mindset to Encourage Innovation in Resolving Problems in the Built Environment: Exploring the Role of Online Gaming Platforms to Deliver Collaborative Learning and Teaching - Shahed Khan; Julie Brunner; David Gibson (Journal of Regional and City Planning, 2018)
Abstract. As educators we seek to set up meaningful graduate attributes to encourage creativity and a drive for innovation among our graduates in order to produce professionals not content with learning how to do more of the same, but who have the courage to push the boundaries of their profession and innovate. Referring to preparatory research on work in progress at Curtin University, we explored the capacity of team teaching using online gaming platform technology. We investigated the feasibility of engaging teams of students in practical applications of theoretical concepts of communicative and collaborative planning and decision-making, along with the dynamics and politics of community consultation in a pluralistic society. We ascertained the potential of developing students' interpersonal and intercultural skills to develop collaborative partnerships through engagement with fellow students and a wide range of stakeholders/partners, simulating real-life situations using serious gaming platforms. It is contended that through a collaborative and experiential learning-approach to teaching and by employing state-of-the-art online gaming/teaching platforms, we could enable students to deal with real-life issues in simulated and sufficiently supervised conditions to encourage creativity and risk taking. This would encourage students to strive for creativity in solving contextual problems in their search for innovative solutions to complex and wicked problems. It is also contended that state-of-the-art delivery of curricula could free up academics during teaching sessions to concentrate on inspiring students to explore innovative and creative solutions for these problems.Keywords. Creativity, innovation, collaborative learning and teaching, online gaming platform, wicked problemsAbstrak.Sebagai pengajar kita berupaya membentuk lulusan yang berkarakter dengan mendorong upaya kreatif dan inovatif pada siswa sehingga terbentuk lulusan profesional yang tidak hanya ahli dalam melakukan hal yang sama secara berulang, tetapi juga memiliki keberanian untuk berinovasi dan mendobrak batas-batas profesi mereka. Mengacu pada persiapan pekerjaan yang sedang berjalan di Curtin University, kami meneliti kapasitas pembelajaran berkelompok dengan menggunakan platform teknologi permainan daring. Kami menyelidiki potensi pelibatan kelompok-kelompok siswa secara langsung dalam penerapan konsep teoetisi perencanaan komunikatif dan kolaboratif, serta pengambilan keputusan dalam dinamika dan politik musyawarah pada kelompok masyarakat yang bersifat majemuk. Kami meneliti bagaimana potensi pengembangan keterampilan interpersonal dan interkultural masing-masing siswa dapat berkontribusi dalam pengembangan kemitraan kolaboratif melalui pelibatan antar sesama siswa dengan berbagai pemangku kepentingan dalam simulasi situasi kehidupan nyata menggunakan platform game yang serius. Melalui pembelajaran dengan pendekatan yang kolaboratif dan eksploratif, serta pemahaman pengalaman pengajaran menggunakan platform teknologi permainan daring, siswa diharapkan sapat lebih memahami maslaah di lapangan. Dalam kondisi yang disimulasikan dan diawasi dengan baik, siswa didorong untuk lebih kreatif dan berani dalam mengambil risiko. Kondisi ini diharapkan mampu mendorong siswa untuk berupaya lebih keras untuk memecahkan masalah kontekstual secara kreatif dan menemukan solusi yang inovatif untuk masalah yang kompleks. Penyampaian materi kurikulum dan pengalaman tentang  pembelajaran dengan platform teknologi permainan daring ini diharapkan memberi kebebasan yang lebih bagi pengajar untuk fokus pada siswa yang menginspirasi dalam lebih menggali solusi yang inovatif dan kreatif untuk masalah tersebut.Kata kunci. Kreativitas, inovasi, pembelajaran dan pengajaran kolaboratif, platform game online, masalah kompleks.